Amoebiasis pada Kambing di Kecamatan Tilongkabila, Gorontalo - Nugroho, Tri Ananda Erwin (Gorontalo Journal of Equatorial Animals, 2024)
This research aims to determine the situation of Amoebiasis in goats in Tilongkabila District, Gotontalo. The sample used was goat feces. Samples were taken randomly from 86 samples in each village in Tilongkabila District, Gorontalo. Stool samples are collected by means of rectal palpation and/or taking feces that have just come out when the goat defecates. Examination of feces samples uses the native method, sedimentation method and flotation method. The results of the examination using a binocular microscope with objective magnification of 10x and 40x, found Entamoeba sp. oocysts, which were sporulating. A total of 7 goat feces were found to contain oocysts from Entamoeba sp. Thus, the proportion of positive cases of Amoebiasis in goats in Tilongkabila District is 8.14%.